If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 10 + -3y = 0 Reorder the terms: 10 + Y + -3y = 0 Solving 10 + Y + -3y = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + Y + -10 + -3y = 0 + -10 Reorder the terms: 10 + -10 + Y + -3y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + Y + -3y = 0 + -10 Y + -3y = 0 + -10 Combine like terms: 0 + -10 = -10 Y + -3y = -10 Add '3y' to each side of the equation. Y + -3y + 3y = -10 + 3y Combine like terms: -3y + 3y = 0 Y + 0 = -10 + 3y Y = -10 + 3y Simplifying Y = -10 + 3y
| 5(t-4)+6(2-f)=5 | | -4x+3x+1=0 | | 2m+8=2(m-4) | | 3k-12=54 | | D=56r | | 2a-4b=2c | | 27-x=17 | | (4m+7)(3m+8)=0 | | (2D^2+D-1)y=x | | 27x=17 | | 3=k-11 | | 5x+3(10x-8)=51 | | 10(w+2)-22=4w+2(9-7w) | | 3(1-2x)=46 | | -15(4w-5)=105 | | 2z*2z+3z=135 | | 8(z+2)-2(z-3)=2(z-4)+3(z-3) | | 2x+16+b+58=180 | | n^2-26n+105=0 | | 16=6r+-7r | | 7s+10=24 | | 72=-9t | | 7h+4=5h-16 | | 430=0.1x^2+2.4x+250 | | 1-9n=-5-3n-9n | | 7+10=24 | | x^5-x^4=12x^3 | | 5(3x-9)-8=5(x-4)+37 | | 2x+16+b+d=180 | | 7+2x=-7x-29 | | m*m+7m-294=0 | | y=(4x-16)(5x+10) |